KONFLIK BATIN TOKOH DALAM CERPEN JURU MASAK KARYA DAMHURI MUHAMMAD: KAJIAN PSIKOANALISIS FREUD DALAM PERSPEKTIF STRATIFIKASI SOSIAL - Armeta Devinka Yola Yogama; Shely Fauziah Dea Maretta; Salwatus Sholehah; Eni Nurhayati; Muhammad Rokib (STKIP Subang, 2026)
This study aims to describe the inner conflict of Makaji as the main character in the short story Juru Masak by Damhuri Muhammad through Sigmund Freud’s psychoanalytic perspective and to explain the influence of social stratification on the character’s psychological conflict. This research employed a qualitative approach with a descriptive method. The primary data source was the text of the short story Juru Masak, while secondary data were obtained from books, journals, and other relevant scientific references. Data were collected through reading and note-taking techniques, then analyzed using content analysis. The results show that Makaji’s inner conflict arises from the contradiction between the id, which drives the need for recognition and self-esteem, the ego, which adjusts to social reality, and the superego, which controls behavior based on social norms. The conflict is further strengthened by social stratification that places the profession of a cook in a subordinate position, causing psychological pressure, decreased self-esteem, and an identity crisis. Thus, the character’s inner conflict is not only caused by individual personality dynamics, but also by interactions with the surrounding social construction. This study confirms that literary works are able to represent the